Personalized Learning and Personal Learning Environments in the Era of Generative AI: Theoretical and conceptual notes - Barrios-Pérez, Eduardo Gabriel; Amaya-Melgar, Stephania (Emerging Trends in Education, 2025)
In a complex and changing world, characterized by massive access to information and the use of emerging technologies such as Generative Artificial Intelligence (GAI), it is crucial to review some of the theoretical foundations of learning personalization. This article examines personalized learning through the use of GAI in the context of Personal Learning Environments (PLE), addressing some theoretical and conceptual bases. Throughout the text, it is discussed how theoretical approaches support the adaptation of teaching to the characteristics of the student, emphasizing the importance of designing educational experiences that promote autonomy and self-regulation. Likewise, the role of the interaction between the student and digital environments in the configuration of personalized training paths is highlighted. Finally, the relevance of the concept of learning personalization in the context of current education is reflected upon.